PERANCANGAN GAME DESAIN "RETURN OF THE AJI SAKA" SEBAGAI UPAYA PELESTARIAN AKSARA JAWA - Kuriawan Ganda Saputra; Asmoro Nurhadi Panindias (Texture:Art and Culture Journal, 2021)
This design aims to make games as a means of education, especially for the younger generation. This design focuses on game design by incorporating historical elements such as Javanese script. The process of designing the game "Return of the Aji Saka" is one of the approaches to learning about culture, especially Javanese script. This design method uses a sequential approach, where a progress as air flows through the phases namely planning, gathering the necessary requirements, knowledge, concepts, and designs. The results of this design can be in the form of promotional media such as artbooks, exhibition booths, online advertising as top-line media (Above the line) and posters, X-banners, stickers, T-shirts, mugs, pins, key chains as bottom-line media (Below the line). line). The design of this game is expected to increase a sense of concern for the younger generation of cultural preservation, especially Javanese script. In addition, it is expected to be an alternative for teenagers to learn Javanese script culture in the digital era like today.